Salivary biomarkers of obstructive sleep apnea syndrome in children. Issue 11 (29th January 2014) - Patacchioli, Francesca R.; Tabarrini, Alessandra; Ghiciuc, Cristina M.; Dima‐Cozma, Lucia Corina; Prete, Anna; Bianchini, Carlotta; Nicoletti, Ferdinando; Gozal, David; Villa, Maria P.
Summary Objectives The present pilot study was performed to evaluate the HPA axis and ANS activity by measuring salivary cortisol and α‐amylase diurnal trajectory and production, respectively, in mild or moderate‐to‐severe (MS) OSA‐affected, but otherwise healthy, children. Moreover, a correlative analysis was performed between the salivary biomarker concentrations and the PSG variables characterizing the OSA severity. Methods We studied 27 consecutive OSA patients (13 mild OSA; 14 MS OSA) and seven healthy children who were enrolled as controls by collecting salivary samples and measuring cortisol and α‐amylase levels using enzyme‐linked bioassays. Results Compared with controls, both mild and MS OSA children showed: (1) increased salivary cortisol diurnal production, (2) maintenance of the physiological circadian activity of the HPA axis, and (3) no changes in α‐amylase diurnal trajectory and production. In addition, morning salivary cortisol concentrations was negatively associated with the disease severity in the MS OSA group. Conclusions OSA is associated with dysregulation of the HPA axis activity in children, the latter potentially underlying some of the adverse consequences of the disease. Pediatr Pulmonol. 2014; 49:1145–1152. © 2014 Wiley Periodicals, Inc.